2018
DOI: 10.1016/j.apor.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical vertical-axis tidal-current-turbine wake model using axial momentum theory with CFD corrections

Abstract: The wake from a tidal current turbine has a significant impact on a tidal farm. A single turbine wake would affect the turbine located adjacent or downstream. Two equations are proposed to predict the mean velocity within the wake of a vertical-axis turbine. The first equation used to predict the efflux velocity is derived based on the axial momentum theory and dimensional analysis. Efflux velocity is the minimum velocity closest to the turbine downstream. The second equation used to predict the lateral veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…However, the outside tail of the sand dune is a little longer than the inside tail. This is due to the wake asymmetry of Darrieus-type tidal current turbine which has been proposed in paper [17]. In summary, the turbine model used in our experiments is small scale model compared with real tidal current turbine under the constraints of the experimental setup.…”
Section: Scaling Effects Of Experimental Setupmentioning
confidence: 92%
See 2 more Smart Citations
“…However, the outside tail of the sand dune is a little longer than the inside tail. This is due to the wake asymmetry of Darrieus-type tidal current turbine which has been proposed in paper [17]. In summary, the turbine model used in our experiments is small scale model compared with real tidal current turbine under the constraints of the experimental setup.…”
Section: Scaling Effects Of Experimental Setupmentioning
confidence: 92%
“…However, the outside tail of the sand dune is a little longer than the inside tail. This is due to the wake asymmetry of Darrieus-type tidal current turbine which has been proposed in paper [17].…”
Section: Scaling Effects Of Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the empirical equation could estimate the seabed scour of a tidal turbine within a 30% error range. Based on Hill et al [22], and Chen [38] results, the statistical functions using correlation coefficient (R), mean absolute error (MAE), root mean squared error (RSME), and scatter index (SI) in Equations (22)- (25) [40][41][42] were calculated to evaluate the performance and accuracy of Equation (19).…”
Section: Equation Used To Predict Maximum Scour Depth For Tidal Turbinementioning
confidence: 99%
“…The rotating propeller releases energy into the water through the production of forward thrust, and a turbine extracts energy from the water through rotations. Lam et al and Ma et al [18,19] found that strong shadowing effects appeared on the turbine through the analysis of experimental and numerical results. Chen and Lam [5] studied the shadowing effect of a turbine rotor and showed that the velocity of a slipstream is accelerated by about 105%.…”
Section: Introductionmentioning
confidence: 99%